STIMULASI MUROTAL AL QURAN TERHADAP NILAI GLASGOW COMA SCALE PADA PASIEN STROKE ISKEMIK - Arif Setyo Upoyo; Helwiyah Ropi; Ria Sitorus (Indonesian Journal of Applied Sciences, 2011)
Stroke is main cause death in the world. The problem stroke patient is decrease of level consciousness that caused by low perfusion in reticular activating system. The aim of research identify the effect of stimulation murotal Al Quran toward increasing score of Glasgow Coma Scale (GCS) at ischemic stroke patient. Design research used quasi experiment with pre and post control group design. The total of sample were 38 patients who taked randomized. Intervention group got stimulation murotal Al Quran 30 minutes a day for 3 days. Assesment GCS was done in the first and the third day. Data was analyzed by Wilcoxon and Mann Whitney test. There were significant difference of GCS score before and after intervention (p=0.034) and significant difference of increasing GCS score between intervention and control groups (p=0.013). Stimulation murotal Al Quran had significant effect in increasing GCS score. it is recommended at ischemmic stroke patient with decrease level of consciousness. ****Stroke merupakan penyebab kematian terbesar di dunia. Masalah pasien stroke di unit keperawatan kritis adalah penurunan kesadaran akibat penurunan perfusi pada  reticular activating system. Tujuan penelitian untuk mengetahui pengaruh stimulasi murotal Al Quran terhadap peningkatan kesadaran pasien stroke iskemik. Desain penelitian adalah pre and post tes control group design. Sampel 38 pasien stroke iskemik diambil secara random. Kelompok intervensi mendapatkan stimulasi murotal Al Quran 30 menit sehari selama 3 hari. Penilaian GCS dilakukan di hari pertama dan ketiga. Data dianalisis dengan Wilxocon dan Mann Whitney test. Hasil yang didapatkan adalah terdapat perbedaan nilai GCS yang bermakna sebelum dan setelah intervensi (p = 0,034). Terdapat perbedaan peningkatan nilai GCS yang bermakna antara kelompok intervensi dan kelompok kontrol (p = 0.013). Stimulasi dengan memperdengarkan murotal Al Quran mempunyai pengaruh positif dalam meningkatkan kesadaran pasien stroke iskemik, sehingga direkomendasikan pada pasien stroke iskemik yang mengalami penurunan kesadaran.